2010
DOI: 10.1590/s0103-84782010005000020
|View full text |Cite
|
Sign up to set email alerts
|

Extensão máxima de retalho pediculado de omento maior através de túnel subcutâneo para ossos longos em cães

Abstract: IIExtensão máxima de retalho pediculado de omento maior através de túnel subcutâneo para ossos longos em cães

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…The use of the greater omentum flap at the fracture site may have contributed to the increased reach and action of the antimicrobial agents for the treatment of the infection, and also to the improved circulation of neutrophils, macrophages, fibroblasts, and endothelial cells also allowing and supporting the drainage and filling of the empty space, Baltzer et al (2015), in a retrospective analyzes, compared two groups of radius fracture in small breed dogs, on one of the groups they used only internal fixation, and on the other one, used internal fixation with greater omentum flap, they observed a shorter consolidation time in the second and shorter median time to healing, concluding that the vascularization of the greater omentum did not suffer any apparent damage, after its passage through the subcutaneous space, guaranteeing its full performance at the fracture site (Ito et al, 2010). Some complications cited by literature, using omentum in another site outside of the abdomen are erythema and subcutaneous edema (Baltzer et al 2015), which were not found in the present case, maybe it happened as a hyper sensibility reaction in some patients and our patient did not show that.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of the greater omentum flap at the fracture site may have contributed to the increased reach and action of the antimicrobial agents for the treatment of the infection, and also to the improved circulation of neutrophils, macrophages, fibroblasts, and endothelial cells also allowing and supporting the drainage and filling of the empty space, Baltzer et al (2015), in a retrospective analyzes, compared two groups of radius fracture in small breed dogs, on one of the groups they used only internal fixation, and on the other one, used internal fixation with greater omentum flap, they observed a shorter consolidation time in the second and shorter median time to healing, concluding that the vascularization of the greater omentum did not suffer any apparent damage, after its passage through the subcutaneous space, guaranteeing its full performance at the fracture site (Ito et al, 2010). Some complications cited by literature, using omentum in another site outside of the abdomen are erythema and subcutaneous edema (Baltzer et al 2015), which were not found in the present case, maybe it happened as a hyper sensibility reaction in some patients and our patient did not show that.…”
Section: Discussionmentioning
confidence: 98%
“…Omentum can preserve its immunogenic and angiogenic capacity as well as its potential of drainage even in distant places when used as flap through the subcutaneous, being able to potentiate several surgical procedures (Ito et al, 2010). The use of the omentum properties for treatment on biologically inactive nonunion associated with chronic osteomyelitis as reported by McAlinden et al (2009), are not common in the consulted literature, so the present report aimed to describe step by step the success of its use in the treatment of a young dog femoral septic nonunion case.…”
Section: Introduction mentioning
confidence: 99%
“…Inúmeros relatos clínicos e experimentais investigam as capacidades do omento quanto à neovascularização, à drenagem linfática, à função imune e de adesão (Ito et al, 2010). Resultados significativos foram descritos nas diferentes funções e também como adjuvante na cicatrização óssea em cães (Ferrigno et al, 2010;Ree et al, 2018) e no tratamento da osteomielite (McAlinden et al, 2009).…”
Section: Introductionunclassified
“…Em decorrência da relativa complexidade e dos riscos das técnicas de utilização do omento como fatores limitantes (Ito et al, 2010), mas principalmente em razão de suas propriedades, a aplicabilidade do enxerto de omento prevalece como objeto de estudo (Ree et al, 2018), um método viável à amputação, em especial como adjuvante no tratamento da osteomielite e não união, pouco descrito em medicina veterinária (Mcalinden et al, 2009;Ferrigno et al, 2010). Nesse âmbito, o objetivo do relato é descrever o reparo cirúrgico utilizando retalho de omento maior pediculado em osteossíntese de tíbia com foco de osteomielite, em um cão jovem de raça gigante.…”
Section: Introductionunclassified
“…Conclui-se que o retalho de omento maior pediculado simples pode alcançar a diáfise tibial, corroborando ITO et al (2010), que funciona como leito vascular para enxertos cutâneos de malha, e confirmando achados de EROL & SPIRA (1980) e ARNOLD et al (1976, ao acelerar o processo de cicatrização óssea devido a sua atividade angiogênica sobre estruturas adjacentes onde é aplicado.…”
unclassified